2001
DOI: 10.1017/s1461145701002644
|View full text |Cite
|
Sign up to set email alerts
|

Monoaminergic function in the pathogenesis of seasonal affective disorder

Abstract: Seasonal affective disorder\winter type (SAD) is characterized by recurrent depressive episodes during autumn and winter alternating with non-depressive episodes during spring and summer. Light therapy with fullspectrum, bright white light has been shown to be effective for this condition. Several hypotheses have been discussed in the literature about the pathogenesis of SAD. The most prominent includes disturbances in central monoaminergic transmission. Evidence can be inferred from studies showing a seasonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 90 publications
(94 reference statements)
0
21
0
4
Order By: Relevance
“…Using Kasper's criteria [13] , 16.4% of our sample were classifi ed as having SAD (winter: 11.6%, summer: 4.2%, fall: 0.53%, spring 0%) and 10.1% as having subsyndromal SAD (winter: 5.9%, summer: 2.7%, fall: 2.1%, spring: 0%). Thus, 26.5% is denoted henceforth 'seasonals'.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Kasper's criteria [13] , 16.4% of our sample were classifi ed as having SAD (winter: 11.6%, summer: 4.2%, fall: 0.53%, spring 0%) and 10.1% as having subsyndromal SAD (winter: 5.9%, summer: 2.7%, fall: 2.1%, spring: 0%). Thus, 26.5% is denoted henceforth 'seasonals'.…”
Section: Resultsmentioning
confidence: 99%
“…[10] suggested that light may exert its effects via normalization of transducin (a G-protein in the retina) levels, which are thought to be reduced in winter depression. The regulation of serotonergic neurotransmission is found to be altered in SAD, which also involves signal transduction via G-proteins [16] . Therefore, it is possible that the altered G-protein signal transduction related with the 825T allele and G ␀ 3s variant could mediate the response to light leading to seasonal variation and the pathophysiology of SAD.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal affective disorder (SAD) is a condition of regularly occurring depressions, beginning in autumn or early winter, with a remission the following spring or summer [36] . Several hypotheses on the pathophysiology of SAD have been proposed, all of which stress the role of decreasing amounts of daylight during the autumn and winter season [36][37][38][39] . Further, there is a marked seasonality in brain serotonin levels with lowest serotonin content in the hypothalamus during the winter season, and changes in the function or effectiveness of serotonin have been suggested to be of importance in the pathogenesis of SAD [38] .…”
Section: Discussionmentioning
confidence: 99%
“…The amount of OPN4 in the cerebellum was 1.21-fold higher in the EL group (P < 0.01), but no differences Transcranial Light Alters Circadian Molecules J Neurol Res. 2017;7(3): [39][40][41][42][43][44][45] were seen in the ML group compared to controls. Additionally, compared to the ML group, the amount of OPN4 was 1.55-fold higher in the EL group (P < 0.001) (Fig.…”
Section: Melanopsin Protein Abundance In the Mouse Hypothalamus And Cmentioning
confidence: 99%
“…Additionally, monoamines play a role in light signaling [40], and also e.g. in SAD symptoms [41]. In order to determine whether transcranial light has direct effects on OPN4 and monoamine expression in the brain at different times of the day, we illuminated mice transcranially either in the morning or in the evening.…”
Section: Introductionmentioning
confidence: 99%